Preparation method of high-aluminum-component AlGaN device structure and high-aluminum-component AlGaN device structure
Patent Information
- Application Number
- CN202611262478.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor materials technology, specifically to a method for fabricating a high-Al-content AlGaN device structure and the high-Al-content AlGaN device structure. Background Technology
[0002] AlGaN (aluminum gallium nitride) ternary alloys have significant application prospects in deep ultraviolet optoelectronic devices and high-power, high-frequency power electronic devices due to their continuously adjustable bandgap (covering 3.4 eV to 6.2 eV) depending on the Al (aluminum) composition. However, the material growth and device fabrication of AlGaN-based devices currently face a series of technical bottlenecks, as follows.
[0003] Currently, AlGaN materials and devices are generally fabricated using heterogeneous substrate epitaxy technology. This is primarily because AlGaN is a ternary alloy, and there is currently no directly usable homogeneous single-crystal substrate. Therefore, existing AlGaN-based material systems typically use heterogeneous substrates such as sapphire, Si (silicon), SiC (silicon carbide), or AlN (aluminum nitride), and first grow an AlN buffer layer on the substrate to alleviate the high-density dislocations and alloy phase separation problems caused by large lattice mismatch between the heterogeneous substrate and the ternary alloy epitaxial layer.
[0004] However, each of the aforementioned heterostructures has its limitations: high-quality AlN buffer layers require high growth temperatures, and Si substrates lack stability at high temperatures; SiC substrates have high manufacturing costs; while AlN substrates are not only expensive but also lack commercially available large-size products. Therefore, in AlGaN devices with high Al content, sapphire substrates are currently considered a viable solution that balances cost and performance.
[0005] In deep ultraviolet LED (light-emitting diode) devices, the active region is usually far from the substrate. To obtain higher crystal quality, a buffer layer and an n-type electron injection layer several micrometers thick are usually grown before the light-emitting active region. Therefore, devices grown directly using conventional MOCVD (metal-organic chemical vapor deposition) technology can still maintain low leakage current and high reliability.
[0006] However, for lateral transistor devices such as HEMTs (High Electron Mobility Transistors), the AlGaN epitaxial layer grown using conventional MOCVD technology exhibits a high dislocation density, especially at the epitaxial layer-substrate interface where large lattice mismatches cause high-density dislocations. Under high electric field conditions, this can lead to significant device leakage current (e.g., ...). Figure 4 (As shown). The leakage problem directly limits the improvement of the breakdown voltage, which prevents the high critical breakdown electric field advantage corresponding to the inherent high bandgap of high Al composition AlGaN materials from being effectively utilized.
[0007] To suppress leakage at the interface between the epitaxial layer and the substrate in AlGaN-based HEMT devices under high electric fields, traditional techniques primarily reduce leakage paths by growing thick AlN films on heterogeneous substrates. However, this approach faces significant challenges in practical implementation: the source-drain spacing of high-voltage devices is typically tens of micrometers, while the thickness of the AlN epitaxial layer grown by MOCVD is generally only 2 to 3 micrometers. Even if the thickness is increased to over 5 micrometers to improve voltage withstand capability, it still represents an order of magnitude difference compared to the lateral dimensions of the device, making it difficult to effectively block lateral leakage channels. Therefore, traditional epitaxial growth methods alone cannot fundamentally solve the aforementioned interface leakage problem.
[0008] In summary, there is still a lack of effective solutions to the leakage problem caused by high-density dislocations at the heterojunction interface in existing AlGaN-based HEMT devices. There is an urgent need for a new device structure or fabrication method that can significantly reduce interface leakage and improve device breakdown voltage. Summary of the Invention
[0009] To address at least one of the aforementioned problems, the inventors conducted extensive research and experiments, discovering that within a tilt angle range of approximately 1°, increasing the growth rate of the AlN buffer layer not only improves surface smoothness but also reduces dislocation density (e.g., Figure 11 and Figure 12 (As shown). Regarding the selection of the substrate tilt angle range, the inventors conducted numerous supplementary experiments and found that when the substrate tilt angle is small, although the AlN material layer grown on it can obtain a smooth surface morphology (this is because the AlN single-atom step width on a small tilt angle substrate is too wide, which is not conducive to the migration of Al atoms and thus makes it difficult to form macrosteps), the dislocations in the grown AlN material layer will not be significantly adjusted by the change in growth rate, and the problem of high dislocation density in high Al composition AlGaN device structures cannot be solved; the inventors also found that when the substrate tilt angle is large, it is difficult to obtain a high smoothness of the epitaxial structure surface by adjusting the growth process, and macrosteps are easily formed (such as... Figure 6As shown in the figure, this leads to increased scattering at the device interface and reduced device performance. Based on the aforementioned findings and experiments, the inventors selected a sapphire substrate with an offset angle ranging from 0.7° to 2°. Furthermore, since the AlN buffer layer and the sapphire substrate are made of different materials, if the AlN buffer layer is grown directly on the sapphire substrate, problems such as lattice mismatch will lead to high-density defects in the AlN buffer layer. To solve this problem, an AlN template layer is typically introduced between the sapphire substrate and the AlN buffer layer. However, when the AlN buffer layer needs to improve its flatness through rapid growth, the AlN buffer layer will introduce tensile stress due to the dislocations annihilated during high-speed growth. To balance the tensile stress introduced by the AlN buffer layer and avoid a large number of dislocations in the AlN buffer layer, the inventors conceived of fabricating an AlN template layer with a flat surface that can introduce compressive stress on an angled sapphire substrate. Therefore, according to one aspect of the present invention, a method for fabricating a high-Al content AlGaN device structure is provided.
[0010] The fabrication method of this high-Al-content AlGaN device structure includes the following steps: S10: Prepare an AlN template layer with a smooth surface that can introduce compressive stress on a sapphire substrate with an off-angle range of 0.7°~2°; S20: An AlN buffer layer with a smooth surface and low dislocation density is prepared on an AlN template layer using low temperature, high 5 / 3 ratio (V / III ratio, molar ratio of group V source to group III source), and high growth rate.
[0011] Rapidly growing an AlN buffer layer on a sapphire substrate with an offset angle ranging from 0.7° to 2° results in a smooth surface and low dislocation density. The tensile stress generated by dislocation annihilation during rapid growth can be balanced by the compressive stress introduced by the AlN template layer. As a result, the high-Al composition AlGaN device structure fabricated by this method has the characteristics of low dislocation density and low stress. This structure not only improves problems such as interface leakage current, but also has a high breakdown voltage.
[0012] In some embodiments, in step S20, the low-temperature, high 5:3 ratio, and high growth rate process for preparing the AlN buffer layer is achieved as follows: temperature is 1100℃~1250℃, 5:3 ratio is 300~3000, and growth rate is 2μm / h~5μm / h, so that the roughness of the AlN buffer layer is less than 1nm. Because the growth rate of the AlN buffer layer is relatively high, it is not conducive to Al atom migration. This allows for two-dimensional growth of the AlN buffer layer on tilted substrates. Consequently, a smooth AlN buffer layer with low dislocation density can be formed on an AlN template layer that can introduce compressive stress and is prepared on a sapphire substrate with a tilt angle ranging from 0.7° to 2°. Furthermore, controlling the lower limit of the temperature can avoid the problem of poor crystal quality due to low temperature. Controlling the upper limit of the 5:3 ratio can avoid problems such as excessive pre-reaction and difficulty in increasing the growth rate due to an excessively high 5:3 ratio and excessive ammonia. At the same time, controlling the lower limit of the 5:3 ratio can avoid problems such as step formation due to a low 5:3 ratio. Moreover, controlling the upper limit of the growth rate can avoid the problem of excessive requirements on the growth equipment due to excessively fast growth rate and the risk of decreased crystal quality.
[0013] In some specific embodiments, in the preparation of the AlN buffer layer, the group V source is generally NH3 (ammonia) and the group III source is generally TMA (trimethylaluminum).
[0014] In some specific embodiments, in step S20, the pressure is controlled between 30 mbar and 100 mbar. By controlling the pressure within a lower range, the occurrence of pre-reaction can be reduced.
[0015] In some specific embodiments, in step S20, the AlN buffer layer is prepared using MOCVD.
[0016] Generally, MOCVD is used to balance mass production and high-precision thin film thickness and surface control. However, since sapphire substrates are heterogeneous, during the initial epitaxial growth phase of MOCVD fabrication, significant mismatch exists between the heterogeneous substrate and the epitaxial interface, making it difficult to achieve two-dimensional stress-free coherent growth directly. This results in a large number of dislocations at the heterogeneous interface, which act as leakage channels in the device. In traditional low-voltage devices, the leakage current generated by these channels is small and does not significantly affect device operation. However, under high-field conditions, the high density of dislocations at the substrate interface leads to a dramatic increase in leakage current, causing device failure. To address this issue, the inventors conducted further research and experiments, discovering that ultra-high temperature annealing of the prepared AlN template layer can annihilate a large number of dislocations between the AlN template layer and the sapphire substrate under ultra-high temperature annealing conditions, ultimately eliminating grain boundary dislocations. Therefore, in some embodiments, in step S10, an AlN template layer with a smooth surface and capable of inducing compressive stress is prepared on a sapphire substrate with an offset angle ranging from 0.7° to 2° using a high-temperature sputtering, MOCVD, or HVPE (hydride vapor phase epitaxy) followed by ultra-high temperature annealing process, with a thickness ranging from 200 nm to 500 nm. This is beneficial for reducing dislocations and adjusting the overall strain of the epitaxial wafer. Moreover, high-speed growth of an AlN buffer layer on an AlN template layer with fewer dislocations can further reduce the dislocation density of the structure. At the same time, it can also avoid insufficient compressive strain introduced by ultra-high temperature annealing due to insufficient thickness, resulting in weak dislocation modulation capability of the subsequently grown AlN buffer layer. Furthermore, the surface of the annealed AlN template layer is flat, which can avoid the problem of a significant increase in surface roughness due to excessive thickness, which would lead to poor surface flatness of subsequent epitaxial growth, and the problem of excessive compressive stress that is difficult to balance through the subsequent AlN buffer layer, resulting in significant wafer warping. Furthermore, since the MOCVD method used to grow AlN buffer layers on traditional sapphire substrates typically involves growth temperatures around 1200℃, a large number of dislocations are generated at the interface between the sapphire substrate and the AlN template layer during the growth process due to lattice mismatch and AlN nucleation and island merging. Although sputtered polycrystalline AlN also generates a large number of dislocations at the interface due to grain inconsistency, the inventors discovered that ultra-high temperature annealing after sputtering allows AlN to be effectively reorganized and defects eliminated. The quality of the resulting AlN template layer is superior to that obtained by ultra-high temperature annealing after MOCVD or HVPE (hydride vapor phase epitaxy). Moreover, the strain state of the obtained AlN template layer is more controllable than that of AlN template layers prepared by MOCVD or HVPE methods, which facilitates matching compressive strain for subsequent buffer layers.Therefore, in some preferred embodiments, in step S10, an AlN template layer with a smooth surface and capable of inducing compressive stress is prepared on a sapphire substrate with an offset angle ranging from 0.7° to 2° using a high-temperature sputtering followed by ultra-high-temperature annealing process, resulting in an AlN template layer with a thickness ranging from 200 nm to 500 nm. This not only allows sputtered AlN polycrystalline materials to be reconstituted into high-quality single crystals after ultra-high-temperature annealing, but also enables the Al, N, and O atoms at the interface after the ultra-high-temperature annealing process to possess sufficient energy to overcome the potential barrier under sufficiently high temperatures, thus forming a stable AlON alloy material.
[0017] In some specific embodiments, the sputtering temperature for high-temperature sputtering is 500℃~800℃, for example, 650℃ or 700℃, to avoid crystal instability caused by a low sputtering temperature; and to avoid problems such as high requirements for sputtering equipment and large grains that are not conducive to subsequent ultra-high temperature annealing caused by a high sputtering temperature. Preferably, the sputtering temperature range for high-temperature sputtering is 650℃~700℃. More preferably, the sputtering temperature range for high-temperature sputtering is 700℃.
[0018] In some specific embodiments, the annealing temperature range for ultra-high temperature annealing is 1650℃~1750℃. This avoids the insignificant dislocation annihilation effect caused by a low annealing temperature and prevents severe AlN decomposition and poor surface morphology caused by a high annealing temperature, which would hinder the subsequent growth of a high-flatness, high-quality AlN buffer layer. Although ultra-high temperature annealing leads to a decrease in the surface roughness of the AlN template layer (generally higher than 1nm), the surface roughness can be reduced to below 1nm by the subsequently grown AlN buffer layer. In some preferred embodiments, ultra-high temperature annealing is performed in a nitrogen atmosphere at a pressure slightly higher than atmospheric pressure to suppress AlN desorption and decomposition. Since the thermal decomposition of AlN is a reversible reaction, AlN dissociates at high temperatures to produce aluminum and nitrogen. To suppress the desorption and thermal decomposition of the AlN template layer under high-temperature conditions, preferably, a cover plate is attached to the surface of the AlN template layer during annealing. The cover plate can be another sapphire cover plate or a single-crystal AlN cover plate; a sapphire cover plate is preferred to avoid excessively high production costs. Therefore, the gaseous products of AlN template layer decomposition can be restricted from escaping into the annealing chamber by the sapphire cover plate; moreover, the gas partial pressure inside the interlayer between the sapphire substrate and the sapphire cover plate is increased to approach the AlN decomposition equilibrium partial pressure at that temperature, weakening the driving force of AlN forward decomposition, thereby suppressing AlN decomposition loss.
[0019] In some specific embodiments, the sapphire substrate with an offset angle range of 0.7° to 2° is a planar substrate to avoid quality degradation problems such as high-density dislocations during the growth of the AlN buffer layer due to the presence of patterns on the substrate.
[0020] During the experiment, the inventors also discovered that if the stress state of the prepared epitaxial structure is not controlled, the prepared epitaxial structure may sometimes exhibit significant warping, which increases the difficulty of subsequent device fabrication. To avoid this problem, the inventors conducted further research and experiments, finding that the main reason for the significant warping of the epitaxial structure is the presence of large stress in the epitaxial structure. Through extensive research and experimentation, the inventors also discovered that when the thickness of the AlN buffer layer grown by MOCVD is 5 to 7 times that of the AlN template layer formed by sputtering followed by annealing, the epitaxial strain after the AlN buffer layer growth can be less than 0.2 GPa. Therefore, in some embodiments, in step S20, the thickness of the AlN buffer layer is 5 to 7 times that of the AlN template layer. This not only reduces the structural strain after the epitaxial growth of the AlN buffer layer, but also, driven by the compressive strain of the AlN template layer, dislocations turning in the rapidly growing AlN buffer layer are more likely to interact and annihilate due to the certain thickness of the AlN buffer layer, thereby significantly reducing the dislocation density.
[0021] To further reduce dislocations in the AlN buffer layer and decrease the dislocation density at the source, drain, and gate sites, thereby mitigating the potential impact of leakage current on device breakdown voltage under high-field conditions due to the presence of regions with high dislocation density, the inventors conducted further research and experiments. The experiments revealed that after fabricating the AlN buffer layer using the aforementioned method, the dislocation density in the AlN buffer layer was reduced to as low as 4 × 10⁻⁶. 8 cm -2 It can be estimated that there is one dislocation within a region of approximately 500nm*500nm. Simultaneously, the inventors also discovered that the dislocation tilt of the rapidly grown AlN buffer layer is approximately 40°, requiring further introduction of compressive strain to increase the tilt angle and maximize the probability of dislocation interaction at such a low dislocation density. Based on the aforementioned findings, the inventors conceived of introducing an AlGaN layer onto the AlN buffer layer. Due to the lattice mismatch between the AlGaN layer and the AlN buffer layer, this mismatch can be adjusted by introducing compressive strain into the AlN buffer layer, which currently lacks significant compressive strain, thereby driving dislocation turning and achieving effective dislocation annihilation. Therefore, in some embodiments, after step S20, the following step is also included: S30: An AlGaN dislocation filtering layer with a smooth surface that can drive dislocation interactions propagating in the AlN buffer layer is prepared on the AlN buffer layer using low temperature and high growth rate. S40: Prepare a high-Al content AlGaN channel layer and a high-Al content AlGaN barrier layer on an AlGaN dislocation filter layer.
[0022] In some embodiments, the low-temperature, high-growth-rate process for preparing the AlGaN dislocation filter layer in step S30 is achieved as follows: a temperature of 1000℃~1080℃, a 5:3 ratio of 1500~6000, and a growth rate of 2μm / h~6μm / h, so that the roughness of the AlGaN dislocation filter layer is less than 2nm. Because the growth rate of the AlGaN dislocation filter layer is high, it is not conducive to Al atom migration, thus enabling two-dimensional growth of the AlGaN dislocation filter layer on an inclined substrate. Therefore, while ensuring effective dislocation filtering, the surface smoothness of the AlGaN dislocation filter layer can be guaranteed.
[0023] In some embodiments, the pressure is controlled between 75 mbar and 150 mbar in step S30. Controlling the pressure within a lower range not only reduces pre-reactions but also facilitates two-dimensional planar growth, thereby achieving high-quality growth of the AlGaN dislocation filter layer. Preferably, the growth pressure of AlN is lower than that of AlGaN to reduce the occurrence of pre-reactions during AlN growth.
[0024] In some specific embodiments, in the preparation of the AlGaN dislocation filter layer, when preparing AlGaN, the group V source is generally NH3 (ammonia), and the group III source is generally TMA (trimethylaluminum) and TMG (trimethylgallium).
[0025] In some specific embodiments, in step S30, MOCVD is used to prepare the AlGaN dislocation filtering layer.
[0026] In some embodiments, the AlGaN dislocation filter layer is an Al composition gradient structure, a superlattice structure, or multiple superlattice structures; the single-layer thickness of the AlGaN dislocation filter layer with an Al composition gradient structure is not less than 300 nm, and the Al composition difference between adjacent layers is not less than 0.15; the top of the AlGaN dislocation filter layer with a superlattice structure has a thickness of at least 50 nm and is a bulk structure; the average Al composition difference between adjacent superlattices of the AlGaN dislocation filter layer with multiple superlattice structures is not less than 0.15, and the total thickness of each superlattice structure is not less than 300 nm. Therefore, compressive strain can be introduced through lattice mismatch, which can drive dislocation turning at the interface. When the thickness meets the conditions, effective dislocation annihilation can be achieved, thereby further reducing the dislocation density. Moreover, since the well composition of the superlattice is relatively low and the thickness of the well barrier of the superlattice is generally less than 20 nm, although the periodically set thin-layer superlattice can filter dislocations well, the presence of multiple interfaces can also have an adverse effect on the confinement and transport of charge carriers. Therefore, setting a bulk structure on the top of the superlattice in contact with the channel layer can better confine the channel 2DEG (two-dimensional electron gas).
[0027] In some specific embodiments, the AlGaN dislocation filtering layer of the superlattice structure is an AlGaN / AlN superlattice structure, and the superlattice well-barrier composition difference is not less than 0.3.
[0028] In some embodiments, the high-Al content AlGaN channel layer is prepared using a low-temperature, high 5:3 ratio process. This allows for the two-dimensional growth of the high-Al content AlGaN channel layer.
[0029] In some embodiments, in step S40, the process for preparing the high-Al-content AlGaN channel layer is as follows: the temperature is 950℃~1050℃, the 5:3 ratio is 1500~6000, and the growth rate is 1μm / h~2μm / h (0.3nm / s~0.6nm / s) to obtain a high-Al-content AlGaN channel layer with a thickness of 200nm~400nm, a roughness of less than 2nm, and an Al content between 0.4 and 0.75. The Al content of the last layer of the AlGaN dislocation filter layer is at least 0.1 higher than that of the high-Al-content AlGaN channel layer. By controlling the growth rate, we can avoid Al atoms becoming almost unable to migrate due to excessively high growth rates, which would lead to increased Al composition fluctuations and severely affect 2DEG scattering. Simultaneously, we can avoid increasing the Al source flux, which would lead to increased pre-reactions in the Al source and thus a large number of impurity defects in the epitaxial layer. By controlling the lower limit of thickness, we can avoid excessive band bending due to excessive thickness, which would easily cause electron leakage in the 2DEG. By controlling the upper limit of thickness, we can avoid deteriorating surface roughness due to excessive thickness. By controlling the upper limit of Al composition, we can avoid high Al composition AlGaN channels... Excessively high Al content in the AlGaN layer prevents the formation of an AlGaN dislocation filter layer (for example, when the Al content of the channel layer is 0.75, only one dislocation filter layer can be formed), thus preventing the AlGaN dislocation filter layer from introducing compressive strain. Furthermore, by controlling the Al content of the last layer of the AlGaN dislocation filter layer to be at least 0.1 higher than that of the high-Al-content AlGaN channel layer, the channel layer can form a back barrier due to the higher Al content AlGaN at the bottom, thereby better confining the charge carriers. This is beneficial for improving device performance and enhancing the uniformity of the electric field distribution under high-field conditions.
[0030] In some embodiments, the high-Al-content AlGaN barrier layer is prepared using a low-temperature, high 5:3 ratio process. This allows for the two-dimensional growth of the Al-content AlGaN barrier layer.
[0031] In some embodiments, in step S40, the process for preparing the high-Al-content AlGaN barrier layer is as follows: a temperature of 950℃~1050℃, a 5:3 ratio of 2000~6000, and a growth rate of 0.7μm / h~1.4μm / h (0.2nm / s~0.4nm / s) to obtain a high-Al-content AlGaN barrier layer with a thickness of 15nm~35nm. Since the Al content of the barrier layer is higher (generally more than 0.15 higher than the channel layer) and the barrier is thinner, strictly controlling the growth rate to 0.7μm / h~1.4μm / h can avoid problems such as increased pre-reaction of the Al source and inability of Al atoms to migrate due to excessively high growth rates, leading to increased fluctuations in Al composition and poor thickness uniformity. This allows for the preparation of an Al-content AlGaN barrier layer with high flatness, thickness, and Al composition uniformity.
[0032] In some implementations, the pressure is controlled between 75 mbar and 150 mbar in step S40. By controlling the pressure within a lower range, not only can the pre-reaction be reduced, but it is also beneficial for two-dimensional planar growth, thereby achieving high-quality growth of high-Al content AlGaN channel layers and high-Al content AlGaN barrier layers.
[0033] In some embodiments, in step S40, after growing the high-Al composition AlGaN channel layer and before growing the high-Al composition AlGaN barrier layer, an AlN insertion layer is also grown. During the growth of the AlN insertion layer, the 5 / 3 ratio is controlled to be above 2000 to prepare an AlN insertion layer with a thickness not exceeding 3 nm. This allows for the formation of a steep interface; moreover, the introduction of the AlN insertion layer can improve device performance. In some preferred embodiments, during the growth of the AlN insertion layer, bypass ammonia is switched to increase the 5 / 3 ratio to above 2000.
[0034] In some embodiments, in step S40, MOCVD is used to prepare a high-Al content AlGaN channel layer and a high-Al content AlGaN barrier layer.
[0035] In some embodiments, NH3 is continuously supplied and nitrogen gas is introduced (to reduce Al atom migration) during the growth of all epitaxial layers, and the growth conditions for the next epitaxial layer are switched within 30 seconds before the next epitaxial layer is grown directly. This ensures good surface flatness throughout the epitaxial growth process on the tilted substrate and prevents macrosteps caused by prolonged purging. Furthermore, the inventors discovered that introducing nitrogen gas during the high-speed fabrication of the AlN buffer layer and AlGaN dislocation filter layer further reduces the migration rate of Al atoms, ensuring stable two-dimensional growth of the AlN buffer layer and AlGaN dislocation filter layer.
[0036] In some implementations, after the growth of the high-Al content AlGaN barrier layer is completed, the temperature is first reduced to below 900°C within 90 seconds, and then further cooled (e.g., at a rate of 1°C / s). Since the desorption rate of Ga is very slow below 900°C, it will not affect the epitaxial surface structure, thereby avoiding the high Al content on the surface that would affect the 2DEG performance.
[0037] According to another aspect of the present invention, a high-Al-content AlGaN device structure is provided.
[0038] The high-Al content AlGaN device structure was prepared using the aforementioned method for preparing high-Al content AlGaN device structures.
[0039] This invention introduces sputtered AlN onto a sapphire substrate with a certain tilt angle, followed by ultra-high temperature thermal annealing, and uses high-speed epitaxial growth technology to improve epitaxial flatness while achieving low material dislocation density and low interface dislocation density, thereby realizing high-performance devices (flat surface epitaxy) and high voltage withstand (low defects and leakage current). Attached Figure Description
[0040] Figure 1 This is a schematic diagram of the structure of a high-Al composition AlGaN device according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of a high-Al composition AlGaN device according to another embodiment of the present invention; Figure 3 This is a schematic diagram of the structure of a high-Al-content AlGaN device; where, Figure 3 Figure (a) is a schematic diagram of the structure of a high-Al composition AlGaN device according to another embodiment of the present invention; Figure 3 Figure (b) is a schematic diagram of the structure of a high-Al composition AlGaN device in the prior art; Figure 4 This is a schematic diagram of a high-Al composition AlGaN device structure with high interface dislocations and high through dislocations in the prior art under a high field state. Figure 5 This is a schematic diagram of a high-Al composition AlGaN device structure with low interface dislocations and low through-dislocations according to an embodiment of the present invention under a high field state. Figure 6 A schematic diagram of AFM (atomic force microscopy) showing obvious macrosteps on the surface morphology of AlN grown at low speed on a sapphire substrate with a large tilt angle in the existing technology; Figure 7A schematic diagram of an AFM (AlGaN Surface Mount Technology) for fabricating a high-Al content AlGaN device structure according to an embodiment of the present invention, showing the process of sputtering an AlN template layer on a sapphire substrate with an angle, followed by ultra-high temperature annealing and high-speed growth of an AlN buffer layer to obtain a flat surface. Figure 8 This is a schematic diagram of a TEM (transmission electron microscope) cross-section showing the large number of entangled dislocations at the interface caused by the direct growth of AlN on a sapphire substrate using existing technology. Figure 9 This is a schematic TEM cross-section of a method for fabricating a high-Al content AlGaN device structure according to an embodiment of the present invention, in which an AlN template layer (HTA area) and an AlN buffer layer (reg. area) are sequentially fabricated on a sapphire substrate. Figure 10 A schematic TEM cross-section of an AlGaN dislocation filter layer in an AlGaN device structure, showing how driving dislocation turning reduces dislocation density. Figure 11 This diagram illustrates the relationship between the tilt angle of AlN grown on sapphire substrates at different tilt angles and different growth rates, and the surface roughness of AlN (it can be seen that when the tilt angle of the sapphire substrate is 1° and the AlN growth rate is 2μm / h, the surface roughness of AlN is relatively low). Figure 12 This diagram illustrates the relationship between the tilt angle of AlN grown at different rates on sapphire substrates with different tilt angles, different growth rates, and dislocation densities (it can be seen that when the tilt angle of the sapphire substrate is 1° and the AlN growth rate is 2μm / h, the dislocation density of AlN is relatively low). Figure reference numerals: 11, Sapphire substrate; 110, Silicon substrate; 12, AlN template layer; 13, AlN buffer layer; 14, AlGaN dislocation filter layer; 141, First dislocation filter layer; 142, Second dislocation filter layer; 15, High Al composition AlGaN channel layer; 16, AlN insertion layer; 17, High Al composition AlGaN barrier layer; 181, Source; 182, Drain; 183, Gate; 19, 2DEG. Detailed Implementation
[0041] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.
[0042] It should also be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising" or "including" include not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. The terminology used herein is generally that commonly used by those skilled in the art; in case of any discrepancy with commonly used terminology, the terminology used herein shall prevail.
[0043] In this invention, the term "5 / 3 ratio," also known as the V / III ratio, refers to the molar flow ratio of group 5 elements to group 3 elements.
[0044] Furthermore, for ease of description, spatial relative terms such as “below,” “under,” “lower,” “above,” and “upper” may be used herein to describe the relationship between one element or component and another (or other) element or component as shown in the figure. In addition to the orientation shown in the figure, spatial relative terms are intended to include different orientations of the device during use or operation. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatial relative descriptors used herein can be interpreted accordingly.
[0045] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0046] Figure 1 The diagram schematically illustrates a high-Al composition AlGaN device structure according to a first embodiment of the present invention.
[0047] like Figure 1As shown, the high-Al composition AlGaN device structure includes a sapphire substrate, and an AlN template layer, an AlN buffer layer, an AlGaN dislocation filter layer, a high-Al composition AlGaN channel layer, and a high-Al composition AlGaN barrier layer sequentially grown on the sapphire substrate. The sapphire substrate has an offset angle ranging from 0.7° to 2°, for example, an offset angle of 0.7° to 2° on the c-plane. Generally, since AlN and AlGaN have hexagonal symmetry structures, the substrate offset angle is often used as c-on-m and c-on-a-plane. The thickness of the AlN template layer ranges from 200 nm to 500 nm, and the AlN template layer undergoes ultra-high temperature annealing treatment, with the ultra-high temperature annealing temperature range being 1650℃ to 1750℃. The N-type template layer is prepared by high-temperature sputtering, MOCVD, or HVPE followed by ultra-high temperature annealing, preferably by high-temperature sputtering followed by ultra-high temperature annealing. The sputtering temperature is 500℃~800℃. The AlN buffer layer has a surface roughness of less than 1 nm and is prepared by a method with a temperature of 1100℃~1250℃, a 5:3 ratio of 300~3000, a growth rate of 2μm / h~5μm / h, and a pressure of 30mbar~100mbar. Its thickness is 5 to 7 times that of the AlN template layer. The AlGaN dislocation filter layer has a roughness of less than 2 nm and is prepared by a method with a temperature of 1000℃~1080℃ and a 5:3 ratio of 1500~1500. The AlGaN dislocation filter layer was prepared using a method with a growth rate of 2 μm / h to 6 μm / h and a pressure of 75 mbar to 150 mbar. The AlGaN dislocation filter layer can be an Al composition graded structure, a superlattice structure, or multiple superlattice structures. For AlGaN dislocation filter layers with graded Al composition, the single-layer thickness is not less than 300 nm, and the Al composition difference between adjacent layers is not less than 0.15. For AlGaN dislocation filter layers with superlattice structures, the top layer is at least 50 nm thick and has a bulk structure. For AlGaN dislocation filter layers with multiple superlattice structures, the average Al composition difference between adjacent superlattices is not less than 0.15. The thickness of the high-Al-content AlGaN channel layer is 200 nm to 400 nm. The AlGaN dislocation filter layer has a surface roughness of less than 2 nm, an Al content between 0.4 and 0.75, and the Al content of the last layer is at least 0.1 higher than that of the high-Al content AlGaN channel layer. It is prepared by a method with a temperature of 950℃ to 1050℃, a 5:3 ratio of 1500 to 6000, a growth rate of 1 μm / h to 2 μm / h, and a pressure of 75 mbar to 150 mbar. The high-Al content AlGaN barrier layer is prepared by a method with a temperature of 950℃ to 1050℃, a 5:3 ratio of 2000 to 6000, a growth rate of 0.7 μm / h to 1.4 μm / h, and a pressure of 75 mbar to 150 mbar.
[0048] Rapidly growing an AlN buffer layer on a sapphire substrate with an offset angle ranging from 0.7° to 2° results in a smooth surface and low dislocation density. Furthermore, the tensile stress introduced by the dislocations annihilated during rapid growth in the AlN buffer layer can be balanced by the compressive stress introduced by the AlN template layer. This method leads to high-Al composition AlGaN device structures with low dislocation density and low stress, which can reduce problems such as interface leakage (according to...). Figure 5 As can be seen, in the high-alcohol-content AlGaN device structure of this embodiment, leakage current generated through interface dislocation channels is effectively suppressed in the high-field state because there are no high-density entangled dislocations at the substrate and AlN epitaxial interface.
[0049] In some embodiments, the tilted sapphire substrate is a planar substrate to avoid the problem of quality degradation such as high-density dislocations at the healing interface caused by the large difference in growth rate of each crystal orientation during the growth of the AlN buffer layer due to the presence of patterns on the substrate.
[0050] Figure 2 The diagram schematically illustrates a high-Al composition AlGaN device structure according to a second embodiment of the present invention.
[0051] The main difference between this embodiment and the first embodiment is that: Figure 2 As shown, the high Al composition AlGaN device structure also includes an AlN insertion layer, which is disposed between the high Al composition AlGaN channel layer and the high Al composition AlGaN barrier layer.
[0052] In some preferred embodiments, the thickness of the insertion layer does not exceed 3 nm, and it is prepared by controlling the 5:3 ratio to be above 2000. During the growth of all epitaxial layers, NH3 is continuously supplied, and the growth conditions for the next epitaxial layer are switched within 30 seconds before directly proceeding to the next epitaxial layer. After the growth of the high-Al composition AlGaN barrier layer is completed, the temperature is first reduced to below 900°C within 90 seconds, and then further cooled.
[0053] Figure 3 Figure (a) schematically shows the structure of a high-Al composition AlGaN device according to a third embodiment of the present invention.
[0054] The main difference between this embodiment and the second embodiment is that: the source and drain are fabricated on the high-Al-content AlGaN channel layer, and the gate is fabricated on the high-Al-content AlGaN barrier layer. For example... Figure 3 As shown in Figure (a), the high-Al-content AlGaN device structure of the present invention differs from the high-Al-content AlGaN device structure of the prior art [e.g., Figure 3As shown in Figure (b) of the present invention, the high-Al composition AlGaN device structure of the present invention does not have leakage channels. This is because the AlN template layer of the present invention is sputtered on a sapphire substrate with an offset angle of 0.7° to 2° and then annealed at an ultra-high temperature, resulting in an extremely low dislocation density at the interface between the AlN template layer and the sapphire substrate (e.g., ...). Figure 5 and Figure 9 As shown), this significantly reduces the probability of dislocation line interactions near the interface, thereby greatly reducing lateral leakage current under high field conditions. Furthermore, the dislocation density of the buffer layer prepared at low temperature, high 5:3 ratio, and high growth rate on the low dislocation density template layer is further reduced, and the dislocation density of the dislocation filter layer prepared at low temperature and high growth rate on the buffer layer is further reduced, greatly reducing longitudinal through-dislocations at the source, drain, and gate (combined with...). Figure 5 and Figure 9 As shown, Figure 9 The black line in the middle is a dislocation line, from Figure 9 As can be seen, there are almost no connected dislocations at the interface, and the dislocations continue to bend and disappear at the AlN buffer layer, which greatly suppresses longitudinal leakage. At the same time, it is difficult to form a connected leakage path between the source and the gate to the drain. Even when used in a high field environment, the problem of interface leakage is not easy to occur.
[0055] The reason why leakage channels exist in existing high-Al-content AlGaN device structures is that under high-voltage driving conditions (high voltage applied to the drain, low voltage applied to the source and gate), there are a large number of laterally connected dislocations at the interface between the sapphire substrate and the AlN buffer layer. These dislocations become channels for electron leakage (e.g., Figure 4 As shown), the leakage path is that electrons travel from the source through the semi-insulating high-Al content AlGaN channel layer via paths such as penetrating dislocations, and then laterally propagate at the high dislocation interface between the sapphire substrate and the AlN buffer layer, before traveling from the high-Al content AlGaN channel layer to the drain [e.g.]. Figure 3 [As shown in Figure (b)]; This leakage current is negligible in low-voltage devices with short lengths (source-drain distance), but it is difficult to ignore in high-voltage devices with long lengths. Even under high-field turn-off conditions, because the source and gate are at low potentials and the drain is at high potentials (generally above 2000V), and there are vertically penetrating dislocations (extending upwards from the substrate, such as... Figure 4 and Figure 8 As shown. Figure 8 The black line in the middle is a dislocation line, from Figure 8As can be seen, the dislocation density at the interface is high, with a large number of vertical dislocations. Simultaneously, the tilted and turning dislocations during epitaxial growth form lateral electron transport channels near the substrate-epitaxy interface. This causes electrons to move from the low-potential source and gate along vertical dislocations to the substrate-epitaxy interface, then propagate laterally via the tilted dislocations, and finally move to the drain via vertical dislocations (the movement path is as follows). Figure 4 (The direction of the red line in the diagram), thus causing a leakage phenomenon.
[0056] The following specific examples illustrate the fabrication method of AlGaN device structures with high Al content.
[0057] Example 1 The first step involves using high-temperature sputtering technology to sputter AlN at 650°C on a sapphire substrate with an angle of 1° to the c-plane, followed by ultra-high temperature annealing at 1700°C to form an AlN template layer with a thickness of 350nm. The second step involves using MOCVD technology to prepare an AlN buffer layer on an AlN template layer. The reaction chamber temperature is 1200℃, the reaction chamber pressure is 75mbar, the molar ratio of ammonia to trimethylaluminum is 500, and the AlN growth rate is 2μm / h, in order to prepare an AlN buffer layer with a surface roughness of no more than 1nm.
[0058] In the third step, when preparing the AlGaN dislocation filter layer on the AlN buffer layer, the reaction chamber temperature is 1080℃, the reaction chamber pressure is 133mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is greater than 1500, and the AlGaN growth rate is 2μm / h, so as to prepare an AlGaN dislocation filter layer with a surface roughness of no more than 2nm.
[0059] In the fourth step, when preparing a high-Al content AlGaN channel layer on the AlGaN dislocation filter layer, the reaction chamber temperature is 1050℃, the reaction chamber pressure is 133mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is 1500, and the AlGaN growth rate is 1.5μm / h, in order to prepare a high-Al content AlGaN channel layer with a surface roughness of less than 2nm and an Al content of 0.6, and the Al content of the last layer of the AlGaN dislocation filter layer is at least 0.1 higher than that of the high-Al content AlGaN channel layer.
[0060] In the fifth step, when preparing the high-Al content AlGaN barrier layer on the high-Al content AlGaN channel layer, the reaction chamber temperature is 1050℃, the reaction chamber pressure is 133mbar, the 5:3 ratio is 2000, and the AlGaN growth rate is 1.0μm / h. After the growth of the high-Al content AlGaN barrier layer is completed, the temperature is first reduced to below 900℃ within 90s, and then reduced to room temperature at a rate of 1℃ / s.
[0061] Furthermore, the growth of the substrate to the high Al composition AlGaN barrier layer is a continuous growth process. NH3 is continuously maintained during the growth of all epitaxial layers, and the growth of the next epitaxial layer is directly carried out after the switching of the growth conditions of the next epitaxial layer is completed within 30 seconds.
[0062] Figure 5 This is a schematic diagram of the high-Al composition AlGaN device structure prepared in this embodiment under a high-field state; according to Figure 5 It can be seen that the high-Al composition AlGaN device structure prepared in this embodiment effectively suppresses leakage current generated through interface dislocation channels under high field conditions because there are no high-density entangled dislocations at the substrate and AlN epitaxial interface. Figure 7 This is an AFM schematic diagram of the AlN buffer layer prepared using the preparation method of this embodiment. Figure 7 As can be seen, the AlN buffer layer prepared by the method of this embodiment has a smooth surface with a surface roughness of only 0.6 nm. Figure 9 This is a schematic diagram of the dislocation structure of the high-Al composition AlGaN device structure prepared by the method of this embodiment. Figure 9 It can be seen that the substrate (bottom structure) of the high-Al composition AlGaN device structure prepared by the method of the present invention has an extremely low dislocation density at the interface with the thermally annealed AlN template layer (HTA area, ultra-high temperature annealed region), and there is a significant interaction between them. The dislocation distance exceeds 100 nanometers, far exceeding the tunneling thickness. Furthermore, it can be seen that the regeneration of the AlN buffer layer (Reg. area, regeneration region) on the compressively strained thermally annealed substrate drives the dislocation turning angle to approach 40° (e.g., Figure 9 (The middle arrow indicates the location). Figure 10 A schematic diagram of the structure of nitrides prepared on a heterogeneous substrate, as shown below. Figure 10 As shown, the white lines represent dislocation lines. The bottom layer is a heterogeneous substrate (e.g., a silicon substrate), followed immediately by an AlN buffer layer. The AlN buffer layer contains a large number of dislocations. An AlGaN dislocation filter layer is then grown on the AlN buffer layer. The AlGaN dislocation filter layer includes a first dislocation filter layer and a second dislocation filter layer with different Al composition (Al composition difference > 0.15). Due to the lattice mismatch between the AlGaN dislocation filter layer and the AlN buffer layer, and between the first and second dislocation filter layers, the white dislocation lines are driven to make significant turns at the interfaces. The interaction of these turning dislocations results in a lower dislocation density as the layers go higher. The larger the turning angle, the easier it is for the dislocations to interact, leading to a lower dislocation density. This further reduces the dislocation density of the high-Al composition AlGaN channel layer grown on the low-dislocation-density AlGaN dislocation filter layer.
[0063] Example 2 The first step involves using high-temperature sputtering technology to sputter AlN at 700°C on a sapphire substrate with an angle of 0.7° to the c-plane, followed by ultra-high temperature annealing at 1650°C to form an AlN template layer with a thickness of 200nm. The second step involves using MOCVD technology to prepare an AlN buffer layer on an AlN template layer. The reaction chamber temperature is 1200℃, the reaction chamber pressure is 50mbar, the molar ratio of ammonia to trimethylaluminum is 500, and the AlN growth rate is 2μm / h, in order to prepare an AlN buffer layer with a surface roughness of no more than 1nm.
[0064] In the third step, when preparing the AlGaN dislocation filter layer on the AlN buffer layer, the reaction chamber temperature is 1080℃, the reaction chamber pressure is 100mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is 1500, and the AlGaN growth rate is 2μm / h, so as to prepare an AlGaN dislocation filter layer with a surface roughness of no more than 2nm.
[0065] In the fourth step, when preparing a high-Al content AlGaN channel layer on the AlGaN dislocation filter layer, the reaction chamber temperature is 1050℃, the reaction chamber pressure is 100mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is 1500, and the AlGaN growth rate is 1μm / h, in order to prepare a high-Al content AlGaN channel layer with a surface roughness of less than 2nm and an Al content of 0.4, and the Al content of the last layer of the AlGaN dislocation filter layer is at least 0.1 higher than that of the high-Al content AlGaN channel layer.
[0066] In the fifth step, when preparing the high-Al content AlGaN barrier layer on the high-Al content AlGaN channel layer, the reaction chamber temperature is 1050℃, the reaction chamber pressure is 100mbar, the 5:3 ratio is 2000, and the AlGaN growth rate is 0.7μm / h. After the growth of the high-Al content AlGaN barrier layer is completed, the temperature is first reduced to below 900℃ within 90s, and then reduced to room temperature at a rate of 1℃ / s.
[0067] Furthermore, the growth of the substrate to the high Al composition AlGaN barrier layer is a continuous growth process. NH3 is continuously maintained during the growth of all epitaxial layers, and the growth of the next epitaxial layer is directly carried out after the switching of the growth conditions of the next epitaxial layer is completed within 30 seconds.
[0068] Example 3 The first step involves using high-temperature sputtering technology to sputter AlN at 650°C on a sapphire substrate with an angle of 2° to the c-plane, followed by ultra-high temperature annealing at 1750°C to form an AlN template layer with a thickness of 500nm. The second step involves using MOCVD technology to prepare an AlN buffer layer on an AlN template layer. The reaction chamber temperature is 1200℃, the reaction chamber pressure is 100mbar, the molar ratio of ammonia to trimethylaluminum is 500, and the AlN growth rate is 3μm / h, in order to prepare an AlN buffer layer with a surface roughness of no more than 1nm.
[0069] In the third step, when preparing the AlGaN dislocation filter layer on the AlN buffer layer, the reaction chamber temperature is 1080℃, the reaction chamber pressure is 150mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is 1500, and the AlGaN growth rate is 3μm / h, so as to prepare an AlGaN dislocation filter layer with a surface roughness of no more than 2nm.
[0070] In the fourth step, when preparing a high-Al content AlGaN channel layer on the AlGaN dislocation filter layer, the reaction chamber temperature is 1050℃, the reaction chamber pressure is 150mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is 1500, and the AlGaN growth rate is 2μm / h, so as to prepare a high-Al content AlGaN channel layer with a surface roughness of less than 2nm and an Al content of 0.75, and the Al content of the last layer of the AlGaN dislocation filter layer is at least 0.1 higher than that of the high-Al content AlGaN channel layer.
[0071] In the fifth step, when preparing the high-Al content AlGaN barrier layer on the high-Al content AlGaN channel layer, the reaction chamber temperature was 1050℃, the reaction chamber pressure was 150mbar, the 5:3 ratio was 2000, and the AlGaN growth rate was 1.4μm / h. After the growth of the high-Al content AlGaN barrier layer was completed, the temperature was first reduced to below 900℃ within 90s, and then reduced to room temperature at a rate of 1℃ / s.
[0072] Furthermore, the growth of the substrate to the high Al composition AlGaN barrier layer is a continuous growth process. NH3 is continuously maintained during the growth of all epitaxial layers, and the growth of the next epitaxial layer is directly carried out after the switching of the growth conditions of the next epitaxial layer is completed within 30 seconds.
[0073] Example 4 The difference between this embodiment and Embodiment 1 is that: The steps following the fourth step and the fifth step include: After the high-Al content AlGaN channel layer is prepared, the Ga source is turned off, and during the growth time of the AlN insertion layer, the conditions such as Al source, Ga source, ammonia, temperature and pressure are gradually changed to the growth conditions of the high-Al content AlGaN barrier layer until the AlN insertion layer is grown. Then, the Ga source is turned on to grow the high-Al content AlGaN barrier layer. When preparing the AlN insertion layer, the 5:3 ratio is controlled to be greater than 2000 so that an AlN insertion layer with a thickness of no more than 3 nm can be grown between the high-Al content AlGaN channel layer and the high-Al content AlGaN barrier layer.
[0074] Comparative Example 1 The first step is to sputter AlN at 650°C on an AlN substrate with an angle of 4° to the c-plane, followed by ultra-high temperature annealing at 1700°C to form an AlN template layer with a thickness of 350nm. In the second step, when preparing the AlN buffer layer on the AlN template layer, the reaction chamber temperature is not higher than 1200℃, the reaction chamber pressure is 75mbar, the molar ratio of ammonia to trimethylaluminum is greater than 500, and the AlN growth rate is less than 1μm / h, so as to prepare an AlN buffer layer with macrosteps on the surface.
[0075] In the third step, when preparing the AlGaN transition layer on the AlN buffer layer, the reaction chamber temperature is not higher than 1080℃, the reaction chamber pressure is 150mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium is greater than 1500, and the AlGaN growth rate is less than 1μm / h, so as to prepare the AlGaN transition layer with macrosteps on the surface.
[0076] In the fourth step, when preparing a high-Al content AlGaN channel layer on the AlGaN transition layer, the reaction chamber temperature should not exceed 1050℃, the reaction chamber pressure should be 150mbar, the molar ratio of ammonia to trimethylaluminum + trimethylgallium should be greater than 1500, and the AlGaN growth rate should be 1.5μm / h, so as to prepare a high-Al content AlGaN channel layer with an Al content of 0.6, and the Al content of the last layer of the AlGaN dislocation filter layer should be at least 0.1 higher than that of the high-Al content AlGaN channel layer.
[0077] In the fifth step, when preparing the high-Al content AlGaN barrier layer on the high-Al content AlGaN channel layer, the reaction chamber temperature should not exceed 1050℃, the reaction chamber pressure should be 150mbar, the 5:3 ratio should be greater than 2000, and the AlGaN growth rate should be between 1.0μm / h. After the growth of the high-Al content AlGaN barrier layer is completed, the temperature should be reduced to below 900℃ within 90s, and then cooled down.
[0078] Comparative Example 2 In the first step, when preparing an AlN buffer layer on a flat sapphire substrate with a c-offset of m0.5° using MOCVD technology, the reaction chamber temperature was 1250℃, the reaction chamber pressure was 50mbar, the molar ratio of ammonia to trimethylaluminum was 500, and the AlN growth rate was less than 0.5μm / h, in order to prepare an AlN buffer layer with macrosteps on the surface.
[0079] In the second step, when preparing the AlN epitaxial layer on the AlN buffer layer, the reaction chamber temperature is 1250℃, the reaction chamber pressure is 50mbar, the molar ratio of ammonia to trimethylaluminum is 400, and the AlN growth rate is less than 0.5μm / h, so as to prepare an AlN epitaxial layer with macrosteps on the surface.
[0080] Figure 8 This is a schematic diagram of the AlN epitaxial structure prepared using the method described in this comparative example. Figure 8 It can be seen that a large number of entangled dislocations are generated at the interface between the sapphire substrate and AlN, and the dislocation density at the interface is extremely high. This leads to frequent dislocation interactions and short dislocation distances. Furthermore, these dislocations are generally vertical (without turning angles, because the AlN epitaxial layer is not subjected to compressive stress from the buffer layer, and the dislocations do not have obvious turning points, but rather propagate almost entirely upwards along the vertical direction). Under high-field conditions, they are prone to tunneling, resulting in high leakage current (e.g., ...). Figure 4 (As shown).
[0081] The above descriptions are merely some embodiments of the present invention. Those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention.
Claims
1. A method for fabricating a high-Al content AlGaN device structure, characterized in that, Includes the following steps: S10: Prepare an AlN template layer with a smooth surface that can introduce compressive stress on a sapphire substrate with an off-angle range of 0.7°~2°; S20: An AlN buffer layer with a smooth surface and low dislocation density is prepared on the AlN template layer using low temperature, high 5:3 ratio and high growth rate.
2. The method for fabricating a high-Al content AlGaN device structure according to claim 1, characterized in that, In step S20, the low-temperature, high 5:3 ratio, and high growth rate process for preparing the AlN buffer layer is achieved as follows: temperature is 1100℃~1250℃, 5:3 ratio is 300~3000, and growth rate is 2μm / h~5μm / h, so that the roughness of the AlN buffer layer is less than 1nm.
3. The method for fabricating a high-Al content AlGaN device structure according to claim 2, characterized in that, In step S10, the AlN template layer with a flat surface and capable of introducing compressive stress is prepared on a sapphire substrate with an offset angle of 0.7° to 2° by a high-temperature sputtering followed by ultra-high temperature annealing process, resulting in an AlN template layer with a thickness ranging from 200 nm to 500 nm; the sapphire substrate is a planar substrate.
4. The method for fabricating a high-Al content AlGaN device structure according to claim 3, characterized in that, In step S20, the thickness of the AlN buffer layer is 5 to 7 times that of the AlN template layer.
5. The method for fabricating a high-Al content AlGaN device structure according to any one of claims 1 to 4, characterized in that, Following step S20, the following steps are also included: S30: An AlGaN dislocation filtering layer with a smooth surface and capable of driving dislocation interactions propagating in the AlN buffer layer is prepared on the AlN buffer layer using low temperature and high growth rate. S40: Prepare a high-Al content AlGaN channel layer and a high-Al content AlGaN barrier layer on the AlGaN dislocation filter layer.
6. The method for fabricating a high-Al content AlGaN device structure according to claim 5, characterized in that, In step S30, the low-temperature, high-growth-rate process for preparing the AlGaN dislocation filter layer is achieved as follows: temperature is 1000℃~1080℃, 5:3 ratio is 1500~6000, and growth rate is 2μm / h~6μm / h, so that the roughness of the AlGaN dislocation filter layer is less than 2nm.
7. The method for fabricating a high-Al content AlGaN device structure according to claim 6, characterized in that, The AlGaN dislocation filtering layer is an Al composition gradient structure, a superlattice structure, or multiple superlattice structures. The thickness of a single layer of the AlGaN dislocation filter layer with the Al composition gradient structure is not less than 300 nm, and the Al composition difference between adjacent layers is not less than 0.
15. The top of the AlGaN dislocation filtering layer of the superlattice structure has a thickness of at least 50 nm and is a bulk structure. The average Al group difference between adjacent superlattice groups in the AlGaN dislocation filter layer with multiple superlattice structures is not less than 0.
15.
8. The method for fabricating a high-Al content AlGaN device structure according to claim 7, characterized in that, In step S40, the process for preparing the high-Al content AlGaN channel layer is as follows: the temperature is 950℃~1050℃, the 5:3 ratio is 1500~6000, and the growth rate is 1μm / h~2μm / h, to obtain a high-Al content AlGaN channel layer with a thickness of 200nm~400nm, a roughness of less than 2nm, and an Al content between 0.4 and 0.
75. The Al content of the last layer of the AlGaN dislocation filter layer is at least 0.1 higher than that of the high-Al content AlGaN channel layer. The process for preparing the high-Al content AlGaN barrier layer is as follows: the temperature is 950℃~1050℃, the 5:3 ratio is 2000~6000, and the growth rate is 0.7μm / h~1.4μm / h, so as to obtain a high-Al content AlGaN barrier layer with a thickness of 15nm~35nm.
9. The method for fabricating a high-Al content AlGaN device structure according to claim 8, characterized in that, In step S40, after growing the high Al content AlGaN channel layer and before growing the high Al content AlGaN barrier layer, an AlN insertion layer is also grown. When growing the AlN insertion layer, the 5:3 ratio is controlled to be above 2000 so as to prepare an AlN insertion layer with a thickness of no more than 3 nm. During the growth of all epitaxial layers, ensure that NH3 is continuously supplied and nitrogen is introduced. After switching the growth conditions of the next epitaxial layer within 30 seconds, proceed directly to the growth of the next epitaxial layer. After the growth of the high-Al content AlGaN barrier layer is completed, the temperature is first reduced to below 900℃ within 90s, and then cooled down.
10. A high-Al-content AlGaN device structure, characterized in that, The high-Al content AlGaN device structure is prepared using the preparation method of the high-Al content AlGaN device structure according to any one of claims 1 to 9.